Crowding of international mutual funds - Tanja Artiga González; Teodor Dyakov; Justus Inhoffen; Evert Wipplinger (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
We construct a fund-specific measure of crowding using the equity holdings overlap of 17,364 global funds which are actively managed. Funds in the top decile of crowding underperform the passive benchmark by 1.4% per year. The poor performance cannot be attributed to fees and transaction costs alone. When we explore the economics behind crowding, we establish that the diseconomies of crowding are distinct from the ones associated with size. Among several possible mechanisms, we find support for a) a preference for liquid stocks among crowded funds and b) differences in the propagation of price pressure from flows of connected funds. Our findings reveal that the tendency of managers to follow correlated strategies is a major source of diseconomies in the active fund industry.
Keywords: G15; G23; 330; Mutual funds; crowding; diseconomies of scale